In Vivo Validation of a Computer-Assisted Bowel Length Measurement System - Benjamin F. B. Mayer; Sebastian Bodenstedt; Patrick Mietkowski; Rudolf Rempel; Lena M. Schulte; Stefanie Speidel; Hannes G. Kenngott; Karl F. Kowalewski (Surgical Techniques Development)
(1) Background: The aim of this study was to investigate potential translational factors for optical 3D reconstruction in an in vivo setting using a newly developed computerized bowel length measurement system (BMS) as a real-time application. (2) Methods: The BMS was evaluated in an in vivo porcine experiment for the influence of light source power (Watt), laparoscope-to-bowel distance (cm), bowel rotation, image background, and surgical objects in the image. Endpoints were robustness, calculated as success rate (SR) in percent, and accuracy, defined as relative error (RE) in percent of BMS measurement result to ground truth. (3) Results: A total of 1992 bowel measurements were performed on n = 7 pigs using the BMS. Bowel measurements were robust and accurate regardless of light source power, at a laparoscope-to-bowel distance of 5 cm (SR 100%, RE 18 ± 38.5%), when the small bowel was aligned horizontally (SR 100%, RE 7.3 ± 36.2%) or in the image background (SR 100%, RE 15.2 ± 23.4%), and when no additional instruments were in the image. (4) Conclusions: Applications based on optical 3D reconstruction are feasible for intraoperative use and could enable quantitative laparoscopy.